KARBON KISLOTALARÍ TEMASÍN JAŃA PEDAGOGIKALÍQ TEXNOLOGIYALAR TIYKARÍNDA ÚYRENIW - Utenova, G.U.; Uzaqbergenov, N.J. (SCIENCE and SOCIETY, 2024)
In the article, the use of interactive methods in the teaching of carboxylic acids, the analysis of methodical methods and their importance in order to increase the students’ ability to work and interest in chemistry, and to form their independent work skills done.